The Heterogeneity of Selective Mutism: A Primer for a More Refined Approach - Kearney, Christopher A.; Rede, Melanie (Frontiers in Psychology, 2021)
Selective mutism is a persistent and debilitating psychiatric disorder in which a child fails to speak in situations where speaking is expected. Although listed as an anxiety disorder, the multifaceted and heterogeneous nature of selective mutism indicates that a more accurate conceptualization may be as a neurodevelopmental disorder. This article serves as a primer of historical and clinical presentations, empirical clinical profiles, clinical distinctions, assessment, and treatment related to the complexity of selective mutism. The article includes a brief discussion of selective mutism within a developmental psychopathology perspective with an eye toward reformed efforts for prevention, assessment, and treatment regarding this population.